Evaluation of Malaysian English language teaching textbooks - Mukundan, Jayakaran; Kalajahi, Seyed Ali Rezvani (Australian International Academic Centre, 2013)
Research in materials evaluation has been an important focus in ELT since the 1980s. The objective of the present study is to evaluate the general attributes of the textbooks and to evaluate the learning-teaching content. In this study, 944 male and female English teachers (Year 1 to Year 6 & Form 1 to Form 5) evaluated the English books using a valid and reliable checklist. In terms of general attributes and learning-teaching content of the textbooks, the results showed that Year 1 to Year 6 teachers reported that the current textbooks are ‘highly useful’ to the students, whereas Form 1 to Form 5 teachers contended that the school books are only ‘moderately useful’. The findings of this study can be useful for curricula designers and Ministry of Education as a reference for improving or modifying the textbooks.